Wing to wing, oar to oar : readings on courting and marrying - Kass, Amy A.; Kass, Leon (University of Notre Dame Press, 2000)
"Intended to help young people of marriageable age and their parents think about the meaning, purpose, and virtues of marriage and, especially, about finding the right person with whom to make a life"--Jacket.
Keywords: Courtship -- Miscellanea.; Marriage -- Miscellanea.; Love -- Miscellanea.; Amours -- Miscellanées.; Mariage -- Miscellanées.; Amour -- Miscellanées.; RELIGION / Ethics; Courtship; Love; Marriage; miscellanies.; Trivia and miscellanea; Trivia and miscellanea.; Miscellanées.